Epidemiologyand Management Of Powdery Mildew Of Mustard Caused By Erysiphe Cruciferarum (Journal of Plant Disease Sciences, 2019)
Epidemiological and management study was undertaken of powdery mildew of mustard incited by Erysiphe cruciferarum and results reveled that maximum spore germination of E.cruciferarum occurred at 25±1oC temperature after 10 hours of incubation. Under filed condition average temperature ranges between minimum 9.24oC to maximum 28.65oCand humidity range between morning 55.42 % to evening 30.15 % with 8.74 sunshine hours and 0.71 km/hr wind velocity was ideal condition for development powdery mildew of mustard. Dinocap @0.1% found effective and significantly superior in reducing the disease intensity (9.00%)of powdery mildew of mustard whereas biocontrol agent Ampelomyces quisqualis @0.5 recorded 19.11 % disease intensity. Dinocap resulted in maximum yield (1417 kg/ha) and found at par with Hexaconazole @ 0.1(1376.3 kg/ha) whereas Ampelomyces quisqualis recorded 1096.6 kg/ ha yield of mustard. Highest B:C ratio was recorded in Hexaconazole (2.77) followed by Dinocap (2.73).
Keywords: Powdery mildew; Erysiphe cruciferarum; fungicides; biocontrol agent; mustard